(untitled) (Antologia di Diritto Pubblico, 2023)
This is the reproduction, in the original layout, of a study dedicated by Santi Romano (1875-1947) to parliamentary regulations and published in 1905. The study deals, among other things, with defining the legal nature of parliamentary regulations.